(untitled) (Вісник: Міжнародні відносини, 2021)
Public service broadcasting first emerged in Britain with the advent of the British Broadcasting Company Ltd (BBC) in 1922. After that, the system of organization of television and radio broadcasting, in which control by the state is impossible, spread throughout Europe. Every European society has a history of the emergence and development of public service broadcasting, but usually in democracies they all play the role of social institutions, which, according to the Recommendation of the Parliamentary Assembly of the Council of Europe, aim to "provide society growth of social, political and cultural activity of citizens and cohesion of society ".